2022
DOI: 10.3390/w14050725
|View full text |Cite
|
Sign up to set email alerts
|

Research on Vegetation Coverage Dynamics and Prediction in the Taitema Lake Region

Abstract: The Tarim River is the largest inland river in China, which plays a crucial role in maintaining regional ecological security and carbon cycle/dynamic. However, the “green corridor” in the Taitema Lake region at the lower reaches of the Tarim River has unclear environmental changes and future dynamics due to the influence of the ecological water conveyance. Hence, protecting the “green corridor” at the lower reaches of the Tarim River in China is strategically important not only ecologically but also socially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
1
0
0
Order By: Relevance
“…Specifically, the optimal groundwater level for trees and grass growth was around −3 m. This is consistence with Hao et al (2010) who found that the optimum groundwater level for major plant growth was between −2 and −4 m. Similarly, groundwater level depth and distance from the river were the crucial environmental factors affecting vegetation coverage. The potential vegetation coverage level in the LTRB showed a downward trend with the increase of the distance from the river channel, consistent with the Zuo et al (2022) results. This is due to the ecological water transfer causing a noticeable improvement in the groundwater level in the near‐river zone, while in the far‐river zone, the groundwater level increased less, and consequently, the potential vegetation coverage level decreased with increasing distance from the river channel (Zhu et al 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, the optimal groundwater level for trees and grass growth was around −3 m. This is consistence with Hao et al (2010) who found that the optimum groundwater level for major plant growth was between −2 and −4 m. Similarly, groundwater level depth and distance from the river were the crucial environmental factors affecting vegetation coverage. The potential vegetation coverage level in the LTRB showed a downward trend with the increase of the distance from the river channel, consistent with the Zuo et al (2022) results. This is due to the ecological water transfer causing a noticeable improvement in the groundwater level in the near‐river zone, while in the far‐river zone, the groundwater level increased less, and consequently, the potential vegetation coverage level decreased with increasing distance from the river channel (Zhu et al 2022).…”
Section: Discussionsupporting
confidence: 90%
“…The study area is located on the southeastern shore of the lake (N 39.412433 • , E 88.517855 • , with an average altitude of 800 m). The breeding habitat of plovers is basically a harsh desert composed of desert grassland, sand land, and sand dunes, which is well-preserved with little human disturbance [67,68].…”
Section: Study Areamentioning
confidence: 99%
“…The study area is located on the southeastern shore of the lake (N39.412433°, E88.517855°; with average altitude of 800 m). The breeding habitat of plovers is basically harsh desert composed of desert grassland, sand land and sand dunes which is well-preserved with little human disturbance [73,74].…”
Section: Study Areamentioning
confidence: 99%